Effectiveness of Qr Code-Based Web Media With a Case Method Approach to Improve Students' Abilities in Making Draping Patterns - Erni; Anggraini, Yudhistira; Bahri, Halimul; Tanjung, Nurhayati (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2025)
Draping patternmaking is a crucial skill in the fashion world, yet students often struggle to grasp the concept and its practical application. These difficulties stem from limited time for practical work and the lack of readily accessible learning resources for draping patternmaking. Web technology allows flexible access to learning materials. QR codes enable quick access to learning content that can be tailored to individual students' needs, supporting flexibility and speed in the learning process. The case method approach, which encourages learning based on real-life case studies, is also increasingly relevant in technology-based learning contexts. This study aims to measure the effectiveness of web-based learning media integrated with QR codes and using the case method approach in improving students' skills in draping patternmaking. This research method employed R&D with the ADDIE development model, which consists of five stages: analysis, design, development, implementation, and evaluation. Based on the study results, validation by material experts (91%) and media experts (95%) was categorized as very valid. The average student response rate of 3.44 indicated a positive assessment of the media. Student perceptions of the media's ease of use, clarity, and usefulness were also very positive. The average N-Gain value of 0.65 indicates that the media's effectiveness is in the moderate category. Thus, this media is suitable for use and has proven quite effective in improving students' abilities in draping learning.